Comparing restaurant service failure and recovery between online and offline complaint channels - Chan, Wei Leong (2013)
Customer complaint behavior has been an important issue to both consumer researchers and marketers. Foodservice organizations have developed a number of channels to facilitate customer complaint solicitation. These channels range from the conventional means such as phone, fax, and face-to-face to the innovative ways like e-mail, Facebook, and website. With the advancement in the computer technology,the ease and real time information management, as well as the increasing number of technological savvy consumers, sourcing service problems from the online channels is the future direction. However, it remains a research question to what extent that the customer complaints sourced from the online channels are representative. This research was undertaken to validate the online complaint with the information collected from the offline situation. The validation was executed by qualitatively (to assess the coverage) and quantitatively (to assess the pattern) analyzing the data on service failures and recovery expectations. In addition, the research proposed a new scheme of service failure categorization based on the services marketing mix. The online complaint data were obtained from two locally-established restaurants and categorized through content analysis. On the other hand, interviews were carried out with approximately 400 respondents from the two restaurants. Respondents described their dissatisfactory dining experience, may lodge face-to-face complaint yet no complaint was filed online (is termed offline complaint). The analyses achieved inter-judge reliability values of 0.91 (failure incidents) and 0.93 (recovery expectations) for the online condition and 0.89 (failure incidents) and 0.86 (recovery expectations) for the offline situation. The findings of the study revealed seven and six main categories of service failures and recovery expectation, respectively. The new service failure categorization schemes appeared to be appropriate. Process-, people-, and product-related were the three main categories of service failures but in different sequence for online and offline channels. This study also highlighted the distinctions between upon-failure and after-failure recovery expectations. Corrective and empathetic actions upon service failure were equally important for online complainers. However, empathetic was more critical to offline complainers. Compensatory actions were not as important, especially among the online complainers, as the attention paid by researchers. As for the context of after-failure, management actions were highly expected. Overall, the results of quantitative analysis yielded somewhat different patterns between the online and offline complaints in terms of service failures and recovery expectations. However, the qualitative analysis revealed that online complaints are more extensive and comprehensive than the offline complaints in both the types of service failure and recovery expectations. Hence, online channel could be useful and as the future means for companies to understand service failures and recovery expectations of customers.